Bilateral idiopathic optic perineuritis with severe vision loss: A case report - Teh, Wee Min; Ibrahim, Mohtar; Wan Hitam, Wan Hazabbah (Elsevier, 2015)
Optic perineuritis is an orbital inflammatory disorder that is either idiopathic or secondary to other conditions such as infection or systemic inflammatory disorders. This condition is very similar to demyelinating optic neuritis, but certain features of the history and magnetic resonance imaging findings are characteristic for and aid in the diagnosis of optic perineuritis. Vision loss varies greatly, from minimal clouding of vision up to only light perception. We report a case of a 44-year-old female with idiopathic bilateral optic perineuritis with vision loss of up to no light perception in both eyes. Radio imaging studies were typical of optic perineuritis and she was started on systemic corticosteroids. She responded very well to steroid therapy and achieved nearly complete visual recovery. There had been no relapse despite cessation of therapy.